Treatment of acute bipolar depression - Yu-Chih Shen (Tzu Chi Medical Journal)
Depression is the predominant pole of disability in bipolar disorder and compared with mania/hypomania, has less systematic research guiding the development of treatment especially in its acute phase (acute bipolar depression). The deficiency in the management of the acute bipolar depression largely reflects the natural divergence of opinion resulting from significant knowledge gaps. At present, there are only 3 approved drug treatments for acute bipolar depression: olanzapine/fluoxetine combination, quetiapine (immediate or extended release), and lurasidone (monotherapy or adjunctive to lithium or valproate). Nonapproved agents and nonpharmacologic treatment such as lamotrigine, antidepressants, modafinil, pramipexole, ketamine, and electroconvulsive therapy are often prescribed to treat acute bipolar depression. This article discusses the challenges of diagnosing bipolar depression, and reviews above treatment options for acute bipolar depression.